2019
DOI: 10.2217/fon-2019-0187
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Role for Carbon Therapy in the Treatment of Gynecological Carcinomas? A Systematic Review

Abstract: This Systematic Review summarizes the literatures of clinical trials on the efficacy and safety of carbon ion therapy for gynecological carcinomas. The protocol is detailed in the online PROSPERO database, registration no. CRD42019121424, and a final set of eight studies were included. In the treatment of cervical carcinomas, both carbon ion therapy alone and carbon ion therapy concurrent chemotherapy have presented good efficacy. Besides, the efficacy of inoperable endometrial carcinomas and gynecological mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…In a systematic review of eight clinical studies from NIRS, Wang et al concluded that carbon ion radiotherapy is safe and effective in the treatment for gynecologic cancers. The authors found lower rates of local recurrence at doses higher than 70 GyE for cervical cancer (95).…”
Section: Gynecologic Cancer Cervical Cancermentioning
confidence: 89%
“…In a systematic review of eight clinical studies from NIRS, Wang et al concluded that carbon ion radiotherapy is safe and effective in the treatment for gynecologic cancers. The authors found lower rates of local recurrence at doses higher than 70 GyE for cervical cancer (95).…”
Section: Gynecologic Cancer Cervical Cancermentioning
confidence: 89%
“…Another current barrier to adoption in the United States is the lack of current randomized data to suggest a benefit of CIRT, although the development of a CIRT center in the United States has the potential to further develop new protocols and to advance preclinical research. Currently, early clinical prospective and retrospective studies have suggested both the safety and the efficacy of CIRT for a variety of disease sites, although there remains few phase III protocols [48][49][50][51][52][53][54][55][56][57][58][59][60]. Based on those early studies, multiple protocols are currently enrolling patients internationally [61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OS rates may vary between different MM sites. 5‐y OS rates were 37%‐50% in vulvar, 13%‐32% in vaginal, and 10% in cervical MM cases 41 . Surgery, photon beam RT, chemotherapy, and PD‐1 checkpoint inhibitors were shown to not significantly improve OS rates 42,43 ; however, CIRT shows promising results for treating gynecological MMs.…”
Section: Discussionmentioning
confidence: 99%